(untitled) (Academicia Globe: Inderscience Research, 2022)
The article provides an idea of the fact that agrotechnical measures such as processing, cultivating, fighting diseases and pests among the buds come into play quickly and qualitatively, that is, agrotechnical measures are fully adapted, for example, to achieve high-precision planting of seeds, and that instead of the usual 70-80 kilograms, 35-40 kilograms of seeds of seeds are spent.